Headache as the initial symptom in two cases of multiple myeloma: a case report and literature review - Liu, Denglu; Du, Minghui; Gao, Xiaoyu (Frontiers in Oncology, 2026)
Multiple myeloma (MM) is a hematologic malignancy characterized by clonal proliferation of plasma cells. It typically manifests with bone pain, renal failure, anemia, and hypercalcemia. However, initial presentations can be atypical, potentially leading to diagnostic delays. We present two cases of MM in which the primary presenting symptom was severe and persistent headache. In both cases, headache was the presenting symptom that ultimately led to the diagnosis. The first case was attributed to hyperviscosity syndrome, while the second resulted from an intracranial plasmacytoma with dural involvement. These cases highlight the importance of including hematological malignancies in the differential diagnosis of new, severe, or atypical headaches, particularly when accompanied by nonspecific systemic symptoms such as fatigue or weight loss. Serum protein electrophoresis (SPEP) and the free light chain (FLC) ratio are critical initial investigations for suspected cases. Early recognition of such atypical presentation can significantly reduce diagnostic delay and improve patient outcomes.